Cost–Utility of Angiotensin-Converting Enzyme Inhibitor-Based Treatment Compared With Thiazide Diuretic-Based Treatment for Hypertension in Elderly Australians Considering Diabetes as Comorbidity - Chowdhury, E.; Ademi, Z.; Moss, J.; Wing, L.; Reid, Christopher (Lippincott Williams & Wilkins, 2015)
Abstract: The objective of this study was to examine the cost-effectiveness of angiotensin-converting enzyme inhibitor (ACEI)-based treatment compared with thiazide diuretic-based treatment for hypertension in elderly Australians considering diabetes as an outcome along with cardiovascular outcomes from the Australian government's perspective. We used a cost–utility analysis to estimate the incremental cost-effectiveness ratio (ICER) per quality-adjusted life-year (QALY) gained. Data on cardiovascular events and new onset of diabetes were used from the Second Australian National Blood Pressure Study, a randomized clinical trial comparing diuretic-based (hydrochlorothiazide) versus ACEI-based (enalapril) treatment in 6083 elderly (age ≥65 years) hypertensive patients over a median 4.1-year period. For this economic analysis, the total study population was stratified into 2 groups. Group A was restricted to participants diabetes free at baseline (n = 5642); group B was restricted to participants with preexisting diabetes mellitus (type 1 or type 2) at baseline (n = 441). Data on utility scores for different events were used from available published literatures; whereas, treatment and adverse event management costs were calculated from direct health care costs available from Australian government reimbursement data. Costs and QALYs were discounted at 5% per annum. One-way and probabilistic sensitivity analyses were performed to assess the uncertainty around utilities and cost data.After a treatment period of 5 years, for group A, the ICER was Australian dollars (AUD) 27,698 (€ 18,004; AUD 1–€ 0.65) per QALY gained comparing ACEI-based treatment with diuretic-based treatment (sensitive to the utility value for new-onset diabetes). In group B, ACEI-based treatment was a dominant strategy (both more effective and cost-saving). On probabilistic sensitivity analysis, the ICERs per QALY gained were always below AUD 50,000 for group B; whereas for group A, the probability of being below AUD 50,000 was 85%. Although the dispensed price of diuretic-based treatment of hypertension in the elderly is lower, upon considering the potential enhanced likelihood of the development of diabetes in addition to the costs of treating cardiovascular disease, ACEI-based treatment may be a more cost-effective strategy in this population.